2017
DOI: 10.1007/s00117-017-0258-3
|View full text |Cite
|
Sign up to set email alerts
|

Praktischer Strahlenschutz am Patienten in der radiologischen Diagnostik

Abstract: [6,12,39]. Die durch Röhrenstrommodulati-on und Sektorscan mögliche Dosiseinsparung liegt bei ca. 10 %, die mittlere Dosis der Mamma kann von ca. 10,6 auf 6,1 mGy (40 %) beim Sektorscan bzw. 9,6 mGy (10 %) bei Röhrenstrommodu-lation in z-Richtung gesenkt werden.Durch die Verwendung eines Schilddrüsenschutzes kann eine Reduktion der Organdosis von 8,37 auf 5,78 mGy um 31 %, bzw. durch Verwendung eines Augenlinsenschutzes die entsprechende Organdosis von 0,32 auf 0,22 mGy um ebenfalls 31 % erzielt werden [2]. Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Literature review in databases of Web of Science, PubMed and Scopus and so on indicated that there were few questionnaires, specifically designed for measuring radiation protection capability in the operating room field, and the available questionnaires are intended for measuring limited dimensions such as knowledge of radiation protection [1,[9][10][11][12]. Also, few studies were about radiation protection capability while considering the patient safety against radiation [13,16]. Moreover, the most of the available questionnaires about radiation protection were designed to be used in radiology wards and they are not appropriate and adequate to be used in the operating room, where the sterility rules and some other principles influence radiation protection acts [17][18][19][20][21][22][23][24][25].…”
mentioning
confidence: 99%
“…Literature review in databases of Web of Science, PubMed and Scopus and so on indicated that there were few questionnaires, specifically designed for measuring radiation protection capability in the operating room field, and the available questionnaires are intended for measuring limited dimensions such as knowledge of radiation protection [1,[9][10][11][12]. Also, few studies were about radiation protection capability while considering the patient safety against radiation [13,16]. Moreover, the most of the available questionnaires about radiation protection were designed to be used in radiology wards and they are not appropriate and adequate to be used in the operating room, where the sterility rules and some other principles influence radiation protection acts [17][18][19][20][21][22][23][24][25].…”
mentioning
confidence: 99%